(untitled) (Global Journal of Management and Business Research, 2022)
Guest satisfaction is important because it gives us business and if they are satisfied then it increases the chances of a guest returning to do more business. It generally means how the guest is satisfied with the company products and service. The hospitality industry is a vast category which includes lodging, food and drink service, event planning, theme parks, travel and tourism. It includes hotels, tourism agencies, restaurants and bars. In this review I got to know that how hotel is maintaining guest experience in this pandemic and building the good value in the market. for my research I also conduct a online survey which shows that how employees of Radisson blu Kaushambi is doing their best to maintain the guest expectations and how much they are satisfied working in this situation.